Quiet tourism, the new luxury, an experience in hospitality - Villa-Nova, João Martim (2023)
This study explores “Quiet Luxury” in Portuguese luxury hotels, aiming to understand luxury experiences and key factors guests value, proposing the “Quiet Tourism” module. Methodologically, it analyses 2435 reviews across seven Portuguese luxury hotels, employing qualitative and mixed-method content analyses, using Leximancer. Results reveal that luxury hospitality is increasingly centred around unique, individualised experiences, emphasising superior service and authenticity. The contribution of this research is, at the theoretical level, to build a framework of the current luxury hospitality in Portugal, highlighting the shift towards subtle, customised luxury experiences. On the methodological level, qualitative analysis will further the meanings of luxury hospitality.